Osteochondral Lesions of the Tibial Plafond: A Restorative Procedure for Cystic Defects - Francis Bustos MD; Richard Ferkel MD (Video Journal of Sports Medicine)
Background: Osteochondral lesions of the tibia plafond (OLTPs) are an uncommon problem that can generate pain. Indications: Arthroscopic techniques can provide symptomatic relief and improved outcomes when conservative management has failed. Technique Description: We present our arthroscopic technique for managing osteochondral lesions of the distal tibia with subchondral cyst formation. By addressing the lesion with bone marrow aspirate concentrate mixed with micronized cartilage matrix and sealing with fibrin glue, we achieve stable restoration of the osteochondral lesion in a competitive athlete. Results: This operative intervention has been shown in clinical series to improve American Orthopaedic Foot & Ankle Society ankle-hindfoot scores postoperatively. Discussion/Conclusion: This restorative procedure for OLTP cystic defects has been shown to produce good to excellent results and is a viable, minimally invasive option in the competitive athlete. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.